2007
DOI: 10.1017/s0021859607006867
|View full text |Cite
|
Sign up to set email alerts
|

Effects of soil compaction in potato (Solanum tuberosum) crops

Abstract: SUMMARYSince many soils used for growing potatoes in the UK are likely to be close to their plastic limit for cultivation during early spring, there exists the potential for soil compaction to occur during planting which will restrict root penetration. A series of experiments showed that soil compaction delayed emergence, reduced rate of leaf appearance and ground cover expansion, shortened canopy cover duration and restricted light interception, which combined to reduce tuber yield. Rooting density and maximu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
0
12

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(61 citation statements)
references
References 31 publications
2
47
0
12
Order By: Relevance
“…The effects of compaction and resulting water stress will differ in shallow-rooted and deep-rooted crops ; thus, a deep-rooted crop like alfalfa may respond differently. Lower yields from our shallow treatment may have been caused by shallower available rooting depth, which would lead to inefficiencies in water and nutrient utilization (Stalham et al 2007). Ross (1986) found that subsoiling increased potato yields under very droughty conditions, but had no effects under near optimum water conditions.…”
Section: Crop Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of compaction and resulting water stress will differ in shallow-rooted and deep-rooted crops ; thus, a deep-rooted crop like alfalfa may respond differently. Lower yields from our shallow treatment may have been caused by shallower available rooting depth, which would lead to inefficiencies in water and nutrient utilization (Stalham et al 2007). Ross (1986) found that subsoiling increased potato yields under very droughty conditions, but had no effects under near optimum water conditions.…”
Section: Crop Productionmentioning
confidence: 99%
“…25), when the shallow treatment had 4% emergence compared with 9% for the medium and 8% for the deep. Stalham et al (2007) reported delayed emergence in potato as a result of planting compaction in the United Kingdom. In our study, regardless of soil depth to the compact layer, all treatments had similar emergence by JD 190 (Jul.…”
Section: Crop Productionmentioning
confidence: 99%
“…These factors combined have impaired tuber yield (Stalham et al, 2007). In that research, density of roots and the depth achieved by them were significantly reduced by compaction, especially in areas wherein compaction occurred in more superficial layers (e.g.…”
Section: Resultsmentioning
confidence: 87%
“…The most superficial layer evaluated (0-20 cm) showed no difference for any of the comparisons between treatments, confirming the efficacy of CT for this depth. When considering 1.5 MPa as a reference (Stalham et al, 2007), no limitation for the potato root growth occurred up to 20 cm depth for all treatments. Nevertheless, only DT treatments presented no limiting penetration resistance at 20-40 cm.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation